Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Biologi Siswa SMA - Naimah; Gepri (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aims to examine the effect of the Problem Based Learning (PBL) model on high school students’ Biology learning outcomes. The research employed a quantitative method with a quasi-experimental design, involving 120 students divided into an experimental class (PBL) and a control class (conventional learning). Learning outcomes data were collected through tests that had been validated and tested for reliability. Data analysis was conducted using descriptive statistics and independent t-tests. The results indicate that the average learning outcomes of the experimental class were higher than those of the control class, with a significant difference (p < 0.05). In addition to improving conceptual understanding, PBL enhanced students’ motivation, critical thinking skills, and collaboration abilities. Therefore, PBL is concluded to be an effective learning strategy for improving high school students’ Biology learning outcomes.